Assessing Scientific Literacy of College Students with TOSLS (Test of Scientific Literacy Skills) - Fitriana, Evi; Permatasari, Faudina (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to identify the scientific literacy skills of students at Malang State University based on gender, year of study, and study program. The research method uses quantitative description. The sampling technique uses purposive random sampling. The population of the study is S1 students at Universitas Negeri Malang who are pursuing education programs. The sample consists of 208 students, divided into 62 males and 146 females. The data collected includes the results of scientific literacy tests using the TOSLS (Test of Scientific Literacy Skills) instrument and demographic data from the respondents obtained through questionnaires. The test instrument is divided into nine indicators of scientific literacy, including the ability to identify scientific concepts, evaluate the validity of sources, and interpret graphs. Data analysis was conducted using the KR20 reliability test, Shapiro-Wilk normality test, and non-parametric analysis such as Mann-Whitney and Kruskal-Wallis. The results of the study showed that the average level of success in questions was 73.37%, based on gender, with details of male respondents with a score of 74.38% and female respondents with a score of 72.36%. The level of scientific literacy of students based on the year of study in working on questions decreased from the first year to the third year (first year = 37%; second year = 46%; third year = 17%). There was a difference in the level of success in completing questions statistically based on the study program, which showed significance (H = 47.93; p <0.05). Geography education students' scores in solving test questions were second worst compared to students studying Biology, Physics, and Chemistry, so they had to do more science-based activities in each lecture activity.